2007
DOI: 10.1534/genetics.107.081026
|View full text |Cite
|
Sign up to set email alerts
|

Deletion-Mutant mtDNA Increases in Somatic Tissues but Decreases in Female Germ Cells With Age

Abstract: The proportions of mutant and wild-type mtDNA are crucial in determining the severity of mitochondrial diseases. It has been generally considered that deletion-mutant mtDNA has replication advantages and accumulates with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 35 publications
(50 reference statements)
2
49
0
11
Order By: Relevance
“…Rather, segregation must occur later in female germ cell development without reduction in mtDNA copy number, presumably because of differential replication of mtDNAs during oocyte maturation. Consistent with this conclusion, they point out that mouse models heteroplasmic for highly deleterious mtDNA mutations including an mtDNA 4696-nt deletion (Sato et al 2007) and an ND6 frameshift mutation (Fan et al 2008) produced pups with lower percentages of mutant mtDNAs in successive litters. If the mtDNA variance were entirely determined by segregation and/or selection early in female germline development, then all litters should be generated from oocytes with the same distribution of heteroplasmy levels.…”
Section: Germline Segregation Of Mtdna Heteroplasmymentioning
confidence: 64%
“…Rather, segregation must occur later in female germ cell development without reduction in mtDNA copy number, presumably because of differential replication of mtDNAs during oocyte maturation. Consistent with this conclusion, they point out that mouse models heteroplasmic for highly deleterious mtDNA mutations including an mtDNA 4696-nt deletion (Sato et al 2007) and an ND6 frameshift mutation (Fan et al 2008) produced pups with lower percentages of mutant mtDNAs in successive litters. If the mtDNA variance were entirely determined by segregation and/or selection early in female germline development, then all litters should be generated from oocytes with the same distribution of heteroplasmy levels.…”
Section: Germline Segregation Of Mtdna Heteroplasmymentioning
confidence: 64%
“…On the other hand, a variety of tRNA mutations were transmitted through the maternal lineage (Stewart et al 2008). Studies of mice containing the 4696-bp deletion have also shown a decrease in the levels of deleted mtDNA in female germ cells and their offspring, although the level of deleted mtDNA remained constant or increased in somatic tissues with age (Sato et al 2007). …”
Section: Introduction Of Mtdna Into the Mousementioning
confidence: 99%
“…3) [16,36]. In the case of mito-mice∆ carrying more than 70% ∆mtDNA at birth, the mitomice∆ showed mitochondrial respiration defects and disease phenotypes and consequently died at around 6 months after birth [16,17,[26][27][28][29]41].…”
mentioning
confidence: 99%
“…In the case of mito-mice∆, however, ∆mtDNA is inherited by progeny until at least the third pregnancy, since the amount of ∆mtDNA in eggs decreases with the aging of female mito-mice∆ [36]. In addition, it is difficult to obtain a large population of mito-mice∆ with the same ∆mtDNA load.…”
mentioning
confidence: 99%